(untitled) (Global Journal of Medical Research, 2022)
The present study sought to statistically relate the histological origin and anaplastic behavior of neoplasms diagnosed in the Pathology Unit of the Faculty of Veterinary Medicine and Zootechnics of the University of San Carlos of Guatemala in the years 2015 to 2019 as well as associate race age sex and affected body system A total of 1 162 canine samples were diagnosed and a subsample of 289 cases was determined by systematic stratified random sampling of proportional allocation of each year Regarding histological origin 44 were epithelial neoplasms 29 connective and derivatives 12 other types 4 endothelial and 1 nervous Concerning the anaplastic behavior 51 of neoplasms were benign and 49 malignant Likewise it was determined that the neoplasms affected mostly females pure breeds canines of 7-10 years and that they affect the integumentary system and soft tissues According to the value of the Cram r index V 0 525 it is concluded that there is a moderate level of association between the histological origin of a neoplasm and anaplastic behavior with which it is inferred that the different histological origins have greater or lesser probability to develop a certain tumor behavior